Water And Slurry Bulkheads In Underground Coal Mines: Design, Monitoring, And Safety Concerns (Preprint 06-043) - S. Harteis; D. Dolinar (Society for Mining, Metallurgy & Exploration, 2006)
Many mining operations rely on bulkheads to provide a barrier between impounded water or slurry and active mine workings. However, bulkhead failures could cause and have caused catastrophic flooding that puts the underground workforce at risk. The National Institute for Occupational Safety and Health1 (NIOSH) in collaboration with the Mine Safety and Health Administration (MSHA) is conducting research to evaluate the adequacy of existing design practices for water and slurry bulkheads. A key component of this research effort is documentation of the performance history and design parameters for bulkheads installed in underground coal mines during the last 20+ years. This research is part of a larger effort to develop general design guidelines and procedures for constructing and maintaining bulkheads that will help to ensure their long-term structural integrity, while significantly reducing the inundation risk for miners. This paper presents the results of NIOSH’s research to identify state-of-the-art bulkhead designs, including design criteria, leakage monitoring systems, and emergency warning systems. Underground observations and evaluations of existing bulkheads suggest that the most important design factors influencing their performance are the interface of the bulkhead with the surrounding strata and the potential magnitude of the hydraulic pressure to which they may be subjected. When a bulkhead has failed, leakage has generally been through the surrounding strata or along the bulkhead/strata interface, with the failure potential along the interface increasing with hydraulic head. It was also determined that development of a monitoring program to ensure the long term structural integrity of bulkheads is an important safety consideration. Current monitoring procedures range from weekly visual inspections to constant monitoring via pressure transducers and fluid level indicators. Where possible, these devices are used in conjunction with a computer based mine monitoring system to alert mine personnel when an emergency condition exists at the bulkhead installation.